Statistics for Non-Statisticians - Madsen, Birger; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book was written for those who need to know how to collect, analyze and present data. It is meant to be a first course for practitioners, a book for private study or brush-up on statistics, and supplementary reading for general statistics classes. The book is untraditional, both with respect to the choice of topics and the presentation. The topics were determined by what is most useful for practical statistical work: even experienced statisticians will find new topics or new approaches to traditional topics. The presentation is as non-mathematical as possible. Mathematical formulae are presented only if they are necessary for calculations and/or add to readers$1 (Bunderstanding. A sample survey is developed as a realistic example throughout the book, and many further examples are presented, which also use data spreadsheets from a supplementary website.s
Preface -- 1 Data Collection -- 2 Presentation of Data -- 3 Description of Data -- 4 The Normal Distribution -- 5 Analysis of Qualitative Data -- 6 Error Sources and Planning -- 7 Assessment of Relationship -- 8 Comparing Two Groups -- 9 Appendices -- Index.
Keywords: Statistics; Mathematical statistics; Economics -- Statistics; Statistics; Statistics, general; Statistical Theory and Methods; Statistics for Business/Economics/Mathematical Finance/Insurance.; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law